p38 MAPK Endogenous Inhibition Improves Neurological Deficits in Global Cerebral Ischemia/Reperfusion Mice - Kun Hou; Zhi-cheng Xiao; Hai-Long Dai (Neural Plasticity)
Cerebral ischemia/reperfusion (I/R) injury is a complex pathophysiological process that can lead to neurological function damage and the formation of cerebral infarction. The p38 MAPK pathway has attracted considerable attention in cerebral I/R injury (IRI), but little research has been carried out on its direct role in vivo. In this study, to observe the effects of p38 MAPK endogenous inhibition on cerebral IRI, p38 heterozygous knockdown (p38KI/+) mice were used. We hypothesized that p38 signaling might be involved in I/R injury and neurological damage reduction and that neurological behavioral deficits improve when p38 MAPK is inhibited. First, we examined the neurological damage and neurological behavioral deficit effects of I/R injury in WT mice. Cerebral I/R injury was induced by the bilateral common carotid artery occlusion (BCCAO) method. The cerebral infarction area and volume were assessed and analyzed by 2,3,5-triphenyltetrazolium chloride (TTC) staining. p38 MAPK and caspase-3 were detected by western blotting. Neuronal apoptosis was measured using TUNEL staining. Neurological deficits were detected by behavioral testing. Furthermore, to assess whether these neuroprotective effects occurred when p38 MAPK was inhibited, p38 heterozygous knockdown (p38KI/+) mice were used. We found that p38 MAPK endogenous inhibition rescued hippocampal cell apoptosis, reduced ischemic penumbra, and improved neurological behavioral deficits. These findings showed that p38 MAPK endogenous inhibition had a neuroprotective effect on IRI and that p38 MAPK may be a potential therapeutic target for cerebral IRI.